Rapidly Degrading Hydrogels to Support Biofabrication and 3D Bioprinting Using Cartilage Microtissues - Kelly, Daniel (My University, 2024)
In recent years, there has been increased interest in the use of cellular spheroids, microtissues, and organoids as biological building blocks to engineer functional tissues and organs. Such microtissues are typically formed by the self-assembly of cellular aggregates and the subsequent deposition of a tissue-specific extracellular matrix (ECM). Biofabrication and 3D bioprinting strategies using microtissues may require the development of supporting hydrogels and bioinks to spatially localize such biological building blocks in 3D space and hence enable the engineering of geometrically defined tissues. Therefore, the aim of this work was to engineer scaled-up, geometrically defined cartilage grafts by combining multiple cartilage microtissues within a rapidly degrading oxidized alginate (OA) supporting hydrogel and maintaining these constructs in dynamic culture conditions. To this end, cartilage microtissues were first independently matured for either 2 or 4 days and then combined in the presence or absence of a supporting OA hydrogel. Over 6 weeks in static culture, constructs engineered using microtissues that were matured independently for 2 days generated higher amounts of glycosaminoglycans (GAGs) compared to those matured for 4 days. Histological analysis revealed intense staining for GAGs and negative staining for calcium deposits in constructs generated by using the supporting OA hydrogel. Less physical contraction was also observed in constructs generated in the presence of the supporting gel; however, the remnants of individual microtissues were more observable, suggesting that even the presence of a rapidly degrading hydrogel may delay the fusion and/or the remodeling of the individual microtissues. Dynamic culture conditions were found to modulate ECM synthesis following the OA hydrogel encapsulation. We also assessed the feasibility of 3D bioprinting of cartilage microtissues within OA based bioinks. It was observed that the microtissues remained viable after extrusion-based bioprinting and were able to fuse after 48 h, particularly when high microtissue densities were used, ultimately generating a cartilage tissue that was rich in GAGs and negative for calcium deposits. Therefore, this work supports the use of OA as a supporting hydrogel/bioink when using microtissues as biological building blocks in diverse biofabrication and 3D bioprinting platforms
PUBLISHED
Keywords: microtissue densities; cellular spheroids; organoids; microtissues, 3D bioprinting, support hydrogel, biofabrication, extrusion-based printing, fusion, cartilage